HUBUNGAN LITERASI KESEHATAN DENGAN PERILAKU PENCEGAHAN KOMPLIKASI PENYAKIT PADA PENDERITA DIABETES TIPE 2 - Adinda Wulandari, I Gusti Agung Ayu; Ary Antari, Gusti Ayu; Ayu Suarningsih, Ni Kadek (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024, 2025)
Type 2 Diabetes Mellitus is a chronic metabolic disease that is susceptibility to disease complications. These complications can be prevented by implementing persistent complication prevention behaviors However, not all diabetes patients have good awareness of these preventive behaviors. One of the influencing factors is the patient's health literacy. This study aimed to determine the relationship between health literacy and prevention behavior of disease complications in patients with type 2 diabetes mellitus. This research was a correlational descriptive study with a cross sectional approach. The number of samples participating in this study was 48 respondents who were obtained through a purposive sampling technique. The Functional, Communicative, and Critical Health Literacy (FCCHL) questionnaire was used to measure health literacy and the complication prevention behavior questionnaire to measure respondent behavior. The results of the study showed that 26 respondents (54,2%) had good health literacy and good prevention behavior by 34 respondents (70,8%). This study found that there was a significant corellation between health literacy and disease prevention behavior (p = 0.000 and r = 0.788). Health services are expected to increase the health literacy of diabetes patients to support better preventive behavior.